Pterygodermatites (Multipectines) pluripectinata n. sp. (Spirurida: Rictulariidae), a nematode parasite of the crab-eating fox Cerdocyon thous (Linnaeus, 1766) from Caatinga shrubland, Brazil - Lux Hoppe, E. G. [UNESP]; Araujo de Lima, R. C. [UNESP]; Tebaldi, J. H. [UNESP]; Nascimento, Adjair Antônio do [UNESP] (Cambridge University Press, 2010)
In a parasitological survey of free-ranging Cerdocyon thous (Carnivora: Canidae) from Brazilian Caatinga shrubland, a new species of Pterygodermatites (Multipectines) was recovered from the small intestine of this host. Morphological analysis showed that P. (Multipectines) pluripectinata n. sp. is distinguished from all other congeneric species mainly by the numerous plate-like projections and male caudal morphology and spicular length. There are few records on the occurrence of this genus in Neotropical regions.